Using 14 Years of Satellite Data to Describe the Hydrodynamic Circulation of the Patras and Corinth Gulfs - Basile Caterina; Aurélia Hubert-Ferrari (Journal of Marine Science and Engineering)
In the absence of in situ data, remote sensing becomes one of the most effective methods for analyzing the hydrodynamics of a basin. In the Gulf of Corinth, the lack of in situ information was addressed using 14 years of satellite data from the Copernicus database to investigate the water circulation dynamics of the Gulfs of Patras and Corinth. The combination of satellite observations and Data Interpolating Empirical Orthogonal Function (DINEOF) methods produced comprehensive maps detailing the hydrodynamic patterns in both gulfs. Despite the paucity of some parts of the datasets, the remaining data revealed key hydrodynamic features through their observations. From the western Patras Gulf to the eastern Corinth Gulf, gyres were the dominant features. The Patras Gulf is primarily characterized by a cyclonic gyre, while the Rio–Antirio Strait, which connects the two gulfs, exhibits unique dynamics due to internal wave activity and upwelling events. Currents generated near the strait flow toward the Corinth Gulf, where they are mostly trapped in an anticyclonic gyre near Itea Bay and a cyclonic gyre near Antikyra Bay. Our analysis highlights the unique dynamics of enclosed gulfs connected to the open sea via a strait. In this case, the Corinth Gulf acts as a smaller-scale analog to the Mediterranean Sea, offering insights into similar hydrodynamic behaviors. The updated hydrodynamic data also improve our understanding of sediment transport pathways and the chlorophyll distribution under present and past conditions.